Analisis Portal Struktur Menggunakan Metode Takabeya dan Sap 2000 - Wahyuni, Wahyuni; Munawir, Munawir; Armianda, Riski (Tameh, 2022)
The building structure is the main component that supports the establishment of a building. In analyzing the building structure, either determinate or indeterminate, there are various moment distribution methods. The method used in this research is the Takabeya method and SAP 2000 as a comparison. The purpose of this study is to compare the value of the moment, shear force and axial force of the building structure with the Takabeya and SAP 2000 methods. From the results of the calculation of the internal forces on the first floor, the value is not significant. As for the 2nd floor, on the portal on the edge of the building there is a small difference in value, but not on the central portal which has a difference of up to 20%. From the overall calculation of internal forces, the ratio of moment values is ± 7%, shear force is ± 3%, and the axial force is ± 5%. The difference in internal force results between the Takabeya and SAP 2000 methods is not too large, it shows that the moment distribution for the two moments is almost the same. But for the results of the shear and axial forces which have very large differences in results, this difference is due to the possibility of load distribution at the joint points.